Philippine stock market: What value does of the selected market information hold for Filipino investors? - Delantar, Edna A. (Animo Repository, 2023)
There is a high level of information efficiency in the stock market. An efficient market adjusts security prices quickly and accurately to new information, without having to digest it for very long. Often, the pace of adjustment is remarkably rapid. This study focuses on the importance of market information as assessed by 250 retail investors in the Philippine Stock Market. The participants have active accounts and engaged in active trading with selected stock brokers. At least 18 years old and above (or the age of eligibility to open an account with a broker). The gender of the respondents had no bearing to the study, as long as they expressed willingness to accomplish the questionnaire. Actual data-gathering started from May 2016 to April 2019. The 19 selected information were classified according to macroeconomic factors, fundamental factors and market trading. To measure the importance of information by retail investors, survey instrument were constructed and utilized 5-point interval scale:1 - Not All Important; 2 – Slightly Important; 3 – Neutral; 4 - Moderately Important; 5 - Very Important, Survey questionnaires were delivered to selected stock brokers, to individual investors at the PSE lounge and distributed via FB group page using google form.The majority of investors considered the return on investment, the volume of bid/ask traded, and the P/E ratio to be most important. It is because most of the investors are millennials with less than five years trading experience and prefer to obtain information online.